A pathogenic variant of TULP3 causes renal and hepatic fibrocystic disease - Jafari Khamirani, Hossein; Palicharla, Vivek Reddy; Dastgheib, Seyed Alireza; Dianatpour, Mehdi; Imanieh, Mohammad Hadi; Tabei, Seyed Sajjad; Besse, Whitney; Mukhopadhyay, Saikat; Liem, Karel F. (Frontiers in Genetics, 2022)
Patient variants in Tubby Like Protein-3 (TULP3) have recently been associated with progressive fibrocystic disease in tissues and organs. TULP3 is a ciliary trafficking protein that links membrane-associated proteins to the intraflagellar transport complex A. In mice, mutations in Tulp3 drive phenotypes consistent with ciliary dysfunction which include renal cystic disease, as part of a ciliopathic spectrum. Here we report two sisters from consanguineous parents with fibrocystic renal and hepatic disease harboring a homozygous missense mutation in TULP3 (NM_003324.5: c.1144C>T, p.Arg382Trp). The R382W patient mutation resides within the C-terminal Tubby domain, a conserved domain required for TULP3 to associate with phosphoinositides. We show that inner medullary collecting duct-3 cells expressing the TULP3 R382W patient variant have a severely reduced ability to localize the membrane-associated proteins ARL13b, INPP5E, and GPR161 to the cilium, consistent with a loss of TULP3 function. These studies establish Arginine 382 as a critical residue in the Tubby domain, which is essential for TULP3-mediated protein trafficking within the cilium, and expand the phenotypic spectrum known to result from recessive deleterious mutations in TULP3.